University Students’ Perception on The Implementation of Online Learning During The Covid-19 - M Nurul Ikhsan Saleh; Ratna Sari; Puji Alim (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
The spread of the Coronavirus disease (COVID-19) pandemic in many countries around the world has changed the learning-teaching process in higher education sectors from face-to-face learning to online learning. This study aims to understand undergraduate students’ views on the implementation of online learning during the COVID-19 pandemic. This research was conducted on 4th to 8th-semester students at the Islamic higher education, Universitas Islam Indonesia, using a qualitative case study. Findings of the study have consisted of three broad themes; firstly, the advantages of online learning: increasing technological literacy, flexibility in learning, improving self-ability, being financially efficient, and supported various learning media; secondly, the weaknesses of online learning: heavy tasks, less effective and decreased enthusiasm, little control from the lecturers, and technical problems; thirdly, constructive feedback on the implementation of online learning: the creation of interesting learning videos, fun learning strategies, holding quizzes, notification of lectures to be multiplied, free internet quota, and additional time for working on assignments. The findings reinforce other studies where the implementation of online learning still requires improvements, particularly during the COVID-19 pandemic. This research can be a reference in policymaking. Further research is needed from the perspectives of lecturers and policymakers to complement the findings.